Making information accessible - Monge, F (International Center for Tropical Agriculture, 1979)
A description is given of a new approach to provide information to cassava workers and the creation of a Cassava Information Center, one of a worldwide network of centers providing highly specialized, current information to agricultural researchers. Factors are described that have contributed to the success of this type of centre and their orientation towards the solution of food- production deficits in the world by using a commodity-oriented strategy. The following are analyzed: the relation between information and research; characteristics of the Latin American scientist regarding information production and consumption; publication infrastructure, that in Latin America is another illustration of the vicious circle of under-development; the services offered by the Scientific Information Exchange Unit at the Centro Internacional de Agricultura Tropical (CIAT); and the concept of consolidated information that includes not only the recollection and dissemination of the results of research but also the mechanisms that synthesize these results and integrate them as scientific and technical knowledge to contribute to the advance ofscience and to the solution of problems. (CIAT)